Ações Golden Share: limites do poder de veto (O veto estatal) - Pavezi, Fabiano Esteves de Barros (2014)
A dissertation submitted for completion of Master of Law focuses the analysis of "limits the power of veto actions Golden Share". The Constitution guarantees the right to private property and free enterprise from the operation of economic activity as it thinks fit. The purpose of the particular, to explore certain economic activity has a single purpose, namely, the pursuit of profit and increase your personal wealth. However, in the eagerness of pursuit of profit, knows clearly that these same entrepreneurs do not hesitate to violate the rights of others, including the community. At this time, the state should interfere in economic activity in order to maintain order and social rights. The more relevant the corporate exploited by private, sharper will be the pursuit of profit. Classic examples are the activities that were previously operated by the State and through privatizations, go to the particular domain. The Golden Share is a very effective way for the state to control these abuses. However, such actions have to be used to maintain public interest in these activities most relevant economic and not as a means "political" to interfere in the private sector. Here arises the need to research and study the limits of these proceedings, that the power granted to the State is not being used for another purpose, such as the aforementioned policy